Marketing Strategy Based on Segmenting, Targeting, and Positioning (STP) and Product Life Cycle (PLC) at Selangkah Trip in Malang City - Yaumi Rohmah; Muhammad Nashirul Haq; Ayu Putriana Dewi; Sudarmiatin Sudarmiatin (Universitas Veteran Bangun Nusantara Sukoharjo, 2025)
The tourism industry is growing rapidly along with the increasing public interest in travel. Travel agencies (BPW) play a strategic role in providing quality services for tourists. Selangkah Trip, one of the BPWs in Malang City, faces fierce competition so it requires the right marketing strategy to remain competitive. This study aims to analyze the application of Segmenting, Targeting, Positioning (STP) and Product Life Cycle (PLC) strategies in improving Selangkah Trip's competitiveness. This study uses a qualitative approach with a case study method, where data is collected through in-depth interviews, observation, and documentation. The results of this study at the segmentation stage, the company focuses the market on schools and corporations, by customizing services for each segment, such as economical tour packages for schools and exclusive services for corporations. In the targeting stage, the company selects segments with stable and sustainable demand, with a direct and digital approach to expand market reach. In positioning, Selangkah Trip emphasizes competitive service quality, affordable prices, and unique experiences, such as the concept of camping in Bromo, to strengthen its image as a trusted travel service provider. This research also identifies the implementation of strategies at PLC, where at the introduction stage, the company focuses on introducing services through strategic partnerships and digital marketing. At the growth stage, demand increases through new service innovations, while at the maturity stage, the company strengthens its position with competitive prices and high-quality services. In the decline stage, the company adapts by offering flexible packages and expanding the market for individual travelers to maintain operational sustainability amid economic challenges.